PENGARUH PENDEKATAN BRAIN-BASED TEACHING TERHADAP HASIL BELAJAR KIMIA - Prasetya, Hermawan Agung; Hadisaputro, Subiyanto (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to determine the effect of inquiry method assisted e-module on the student learning outcomes of chemistry. Population in this study is XI grader in Senior High School (SHS) in Kudus, school year 2011/2012. Student learning activity is less varied, so it need to improve the variety methods to help students to be more interested in studying chemistry. The determination of the sample with cluster random sampling system obtained two classes, one class as a experiment class that are treated using the approach of Brain-Based and one as a control class who received treatment using conventional method. The data in this research obtained by documentation, tests, questionnaires, observation method. The result showed that the experimental class had an average of 85,06 and a control class had an average of 79.03. The data analysis, showed that the experimental class is better than the control class, it is shown by t count (3.159)> t table (1.999). The conclusions of this research is the approach of Brain-Based Teaching gave the significant effect on student learning outcomes on colloid chemistry subject, which is indicated by the coefficient of correlation (rb ) of 0.47 and the influence of 22,50%.Keyword: Brain-Based Teaching Approach